Knowledge, distributed leadership and (structured) agency: a view on academic policy curation - Françoise McKay (Journal of Learning Development in Higher Education)
This opinion piece explores some of the experiences encountered by the non-teaching staff responsible for curating academic policy in institutions. As the framework that upholds standards in universities, academic policy bears significant influence on the whole university community. Academic policy can provide stability to institutions – a fact that should not be undervalued given the ‘supercomplex’ (Barnett, 2000) environment in which the workforce now operates. In this light, the opinion piece illustrates the need for a different type of academic policymaking. It also identifies the potential for existing teams to fill this gap. Despite being a function with a long history in universities, teams responsible for the assurance and management of academic quality have generally been overlooked as a mitigating factor against the uncertainty of an ever-changing political and regulatory environment. The author will suggest that, throughout their policy work, Quality professionals are unrecognised catalysts for operational, pedagogic and strategic change. The discussion will underscore their importance as not simply translators but narrators of academic policy. The piece will close with some reflections on the personal, cultural and structural constraints that limit the value that these professionals can bring to their universities. Threats to colleagues' agency should be considered threats to the compliance, agility and general effectiveness of academic policy. The conclusion will suggest some solutions that colleagues may wish to consider. Discussions are contextualised within theories and frameworks related to educational policymaking, the influence of neoliberal government agendas, and the experience of third-space professionals.